Mengubah Paradigma Pembelajaran Ilmu Tafsir: Penerapan Teknologi Untuk Mengatasi Masalah Siswa Dalam Memahami Ayat Al-Qur'an - Husnul Insani Herlado; Kustati, Martin; Amelia, Rezki; Gusmirawati (Cahaya Ilmu Bangsa Institute, 2024)
The development of technology opens up new opportunities in reviving ways of learning Qur'anic tafsir that are more interesting and relevant for the digital generation. in response to the challenges of the digital era that demand more interactive and relevant learning methods, the researcher used a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation studies. The results showed that the utilization of digital tafsir applications, multimedia (infographics, videos, animations), and e-learning platforms had a significant impact in improving students' understanding of the Qur'anic verses. This study explores the application of digital technology in tafsir learning at Madrasah Aliyah Negeri (MAN) 1 Padang Pariaman, focusing on its impact on students' understanding, interest, and independence. Through digital tafsir applications, interactive multimedia and e-learning platforms, tafsir learning is transformed from a mere reading and listening process to a more visual, contextualized and immersive learning experience. The results show that technology not only improves students' understanding, but also fosters their interest and desire to learn independently. It encourages students to think critically, explore the meaning of the Qur'an in their lives, and participate more actively in learning. Although there are challenges in its implementation, such as limited infrastructure and teacher adaptation, the integration of technology in tafsir learning offers tremendous potential to enrich religious education. This article provides fresh insights into how technology can be a bridge for the younger generation to understand the Qur'ānic message more meaningfully.